If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(2/3)(2x+5)=2(1-3x)+16
We simplify the equation to the form, which is simple to understand
(2/3)*(2x+5)=2(1-3x)+16
Simplifying:
( + 0.666666666667)*(2x+5)=2*(1-3x)+16
Reorder the terms in parentheses
multiplication of parentheses
(+1.33333333333x+3.33333333333)=2*(1-3x)+16
Remove unnecessary parentheses
+1.33333333333x+3.33333333333=2*(1-3x)+16
Reorder the terms in parentheses
+1.33333333333x+3.33333333333=+(+2-6x)+16
Remove unnecessary parentheses
+1.33333333333x+3.33333333333=+2-6x+16
We move all terms containing x to the left and all other terms to the right.
+1.33333333333x+6x=+2+16-3.33333333333
We simplify left and right side of the equation.
+7.33333333333x=+14.6666666667
We divide both sides of the equation by 7.33333333333 to get x.
x=2
| 6x+5=5x+8 | | -3(m-6)=-6 | | 2(x-4)5x=7 | | 6x+18=28-4x | | 3x-32=2(40-x) | | 4x+58=10+13 | | n^2+n+92=0 | | 3g=8-7g | | 34+13x=30+22x | | 0.9x-0.3(6-x)=2.4 | | n/10=3/5 | | pn=55 | | 13=-3(21-b)+2(b-2) | | 10x+7=4x-31 | | -4=2(d-3)-8 | | 0=15-3y-7x | | 9z+2-7z=56-7z | | 6x-32=2(40-x) | | -15k+9k=25 | | 2(s+2)+1=9 | | 11(z+3)-4(z-3)=3(z-4)+3(z-4) | | -61n-8=-8 | | 3y+1=x+4 | | 7x+7-8x=3x-3+x | | 5-u=10 | | 3x+4=44-2x | | 2h-h+5=19 | | 6x^3-36x^2-16x+3=0 | | -7a-3=-4a+7 | | 2x+3.3=8.1 | | 3(x+1)+2x=-2x-4(2x+3) | | 13=-7+6x |